2016
DOI: 10.1007/s10162-016-0582-8
|View full text |Cite
|
Sign up to set email alerts
|

Symmetric Electrode Spanning Narrows the Excitation Patterns of Partial Tripolar Stimuli in Cochlear Implants

Abstract: In cochlear implants (CIs), standard partial tripolar (pTP) mode reduces current spread by returning a fraction of the current to two adjacent flanking electrodes within the cochlea. Symmetric electrode spanning (i.e., separating both the apical and basal return electrodes from the main electrode by one electrode) has been shown to increase the pitch of pTP stimuli, when the ratio of intracochlear return current was fixed. To explain the pitch increase caused by symmetric spanning in pTP mode, this study measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 24 publications
1
3
0
Order By: Relevance
“…Our data are broadly consistent with the results of a study by Luo and Wu [ 15 ]. They compared pTP to pTP + 1 masking patterns, both with psychophysical forward masking and a physiological measure (electrically-evoked compound action potentials), showing a small but significant sharpening with pTP + 1.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our data are broadly consistent with the results of a study by Luo and Wu [ 15 ]. They compared pTP to pTP + 1 masking patterns, both with psychophysical forward masking and a physiological measure (electrically-evoked compound action potentials), showing a small but significant sharpening with pTP + 1.…”
Section: Discussionsupporting
confidence: 93%
“…1 ) may not be ideal for minimising spread of excitation. For example, Luo and Wu [ 15 ] have reported that returning current from the adjacent-but-one electrodes can reduce both current spread and the width of forward-masked excitation patterns compared to the standard pTP method. Our intra-cochlear voltage recordings, described below, indicated that leaving two unused electrodes between the central and flanking electrodes can produce reduced current spread compared to ‘standard’ pTP.…”
Section: Introductionmentioning
confidence: 99%
“…For many years, cochlear implant research has made an effort to narrow the electrical field of speech encoding strategies through multipolar stimulation of the cochlea, also known as current focusing. As a proposed solution to poor spectral discriminatory abilities and a way to improve speech recognition in quiet as well as in noise, current focusing can lead to narrower excitation patterns (van den Honert & Stypulkowski 1987; Kral et al 1998; Bonham & Litvak 2008; Landsberger et al 2012; Kalkman et al 2014; Wu & Luo 2016) and improved spectral resolution (Berenstein et al 2008; Landsberger et al 2012; Smith et al 2013); the ability to discriminate percepts in the frequency domain. As spectral discrimination correlates with speech recognition (Henry & Turner 2003; Won et al 2007; Henry et al 2005; Holden et al 2016; Lawler et al 2017; Luo et al 2020), current focusing can potentially lead to improved speech recognition in noise compared to monopolar stimulation (MP) (Srinivasan et al 2013; Arenberg et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…More recently, there has been growing interest in current focusing by using the intracochlear electrodes to ground the stimulating current. With tripolar stimulation, where the adjacent electrodes of the stimulating electrode are used as grounds and the current loop is entirely intracochlear, the spread of the EF can be reduced potentially achieving narrower patterns of stimulated SGNs and improved speech recognition in complex listening situations ( Snyder et al., 2004 ; Srinivasan et al., 2013 ; Padilla and Landsberger, 2016 ; Luo and Wu, 2016 ). However, to reach similar loudness levels as with monopolar stimulation with an extracochlear ground, the stimulating current in tripolar stimulation must be significantly increased ( Landsberger et al., 2012 ), potentially debilitating the beneficial effects of current focusing ( Morris and Pfingst, 2000 ).…”
Section: Introductionmentioning
confidence: 99%